Spark cookbook : over 60 recipes on spark, covering spark core, spark SQL, spark streaming, MLlib, and GraphX libraries /: over 60 recipes on spark, covering spark core, spark SQL, spark streaming, MLlib, and GraphX libraries. (2015) - Yadav, Rishi
No abstract available